Research Methodology :Methods and Techniques - C.R. Kothari (New Age International Publishers, 2018)
This fourth multi colour edition has been made better equipped to make the learning more systematic. More details are added to old chapters keeping in mind the need of advanced data analysis in social science research. The usage of popular statistical package SPSS has also been shown through many examples. It is important to adopt an appropriate methodology in quality research. The present book provides the basic and advanced level discussion on research methodology so that the researchers may become familiar with the art of using research methods and techniques. The book is intended to serve as a textbook for social science students at graduate and postgraduate level. The book can be taken as a well organised guide for researchers in social science and other areas..